PENGARUH STABILITY BALL EXERCISE TERHADAP ACTIVITY DAILY LIVING PADA IBU HAMIL DENGAN KELUHAN NYERI PUNGGUNG BAWAH - Fatmarizka, Tiara; Keumala, Melati ulee (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Background: Changes during pregnancy include changes in posture and lengthening of the abdominal and pelvic muscles, which can affect the musculoskeletal system. As many as 70% of pregnant women in the third-trimester experience lower back pain caused by increasing gestational age changes in the anatomy and physiology of pregnant women, which can cause Activity Daily Living (ADL) or the daily activities of pregnant women to be disrupted. Stability Ball Exercise (SBE) is an exercise that can reduce the intensity of back pain in pregnant women and can increase daily functional activities. Objective: to determine the effect of providing stability ball workouts on Daily Living Activities in pregnant women with complaints of lower back pain in the Kartasura Health Center work area. Method: quasi-experimental with one group pre-test and post-test design. The sample in this study consisted of 23 pregnant women based on inclusion and exclusion criteria. The analysis test used a paired sample t-test to determine the effect of the stability of ball training on daily activities in pregnant women. Dosing three times a week for four weeks. The instrument in this study used a disability rating index measurement questionnaire with 12 question items divided into three parts. The first item contains basic activities of daily living, the second item contains daily physical activities, and the third item contains activities related to heavier work. Results: A significant relationship exists between the pre- and post-DRI results with a p-value <0.001. Conclusion: There is an effect of stability ball workouts on increasing daily living activities in pregnant women with complaints of lower back pain. Keywords: Activity Daily Living; Pregnancy; Stabillity Ball Exercise